2022
DOI: 10.1007/s11837-022-05315-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Silver Nanoferrite and Nanochromite on Physical Properties for High-Frequency and Biomedical Applications

Abstract: In this work, the effects of silver nanoferrite and nanochromite (Ag2Fe2O2, Ag2Cr2O4) were studied using the flash auto-combustion technique. Numerous physical properties were clarified from the different structures determined from the x-ray examination such as lattice parameter the cation dispersion, oxygen parameter, hopping length, and interatomic distance. Among antimicrobial properties, Ag addition to both samples showed high efficacy against both types of tested bacteria (gram-positive and gram-negative)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…It can be manufactured biologically, anthropogenically, and geologically in erosion, volcanoes, fires of forests, burning of charcoal, and industry [ 12 ]. Moreover, nanoparticles can be prepared by different methods such as the solid-state method and wet methods [ 13 17 ]. The easy, low cost, rapid, save time and give high yield method is the Flash auto-combustion technique in which all the investigated samples have been prepared with it [ 18 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can be manufactured biologically, anthropogenically, and geologically in erosion, volcanoes, fires of forests, burning of charcoal, and industry [ 12 ]. Moreover, nanoparticles can be prepared by different methods such as the solid-state method and wet methods [ 13 17 ]. The easy, low cost, rapid, save time and give high yield method is the Flash auto-combustion technique in which all the investigated samples have been prepared with it [ 18 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The third peak in the DSC curve may be due to recrystallization or redistribution of cations. 42 TG-DSC results confirmed that the thermal plasma synthesis HEO nanoparticle exhibits a single phase up to 300 °C; beyond that, a secondary phase was formed. XRD patterns were examined to find the crystal structure of the as-synthesized and annealed HEO powders, as displayed in Figure 3a.…”
Section: Resultsmentioning
confidence: 53%
“…8 . The operational frequency was estimated as follows [ 36 , 37 ]: where γ = 2.8 MHz/G is the gyromagnetic ratio. Table 3 summarizes the results.…”
Section: Resultsmentioning
confidence: 99%